TRANSFORMASI STRUKTURAL TENAGA KERJA MIGRAN ASAL BUTON DI KABUPATEN TELUK WONDAMA - Fita, Nur; Tieneke Rieke, Els; Mamboai, Hans (Sosio Agri Papua, 2025)
The aim of this research is to determine socio-economic changes as measured by the type of work, income and asset ownership in Teluk Wondama Regency. This research uses a descriptive method with case study techniques. This research uses a purposive sampling approach based on the first 3 (three) criteria of residents from Buton, both men and women aged 20 to 39 years at the time the research was conducted. Second is the group of respondents with the above age criteria who migrated to Wondama Regency after 2005, namely after the expansion of Wondama Bay into a definitive Regency. The third are respondents who meet criteria one and two and have experience working as farmers in their area of origin (Buton) before migrating to Wondama Bay. The results of this research conclude that there has been a change in the socio-economic conditions of migrant communities after being in Teluk Wondama Regency. This is known from changes in the type of work, income and asset ownership which is much better in Teluk Wondama Regency when compared to the socio-economic conditions of migrant communities in the area of origin.